2020
DOI: 10.21037/atm.2020.02.175
|View full text |Cite
|
Sign up to set email alerts
|

Global low back pain prevalence and years lived with disability from 1990 to 2017: estimates from the Global Burden of Disease Study 2017

Abstract: Background: Low back pain (LBP) is a common musculoskeletal problem globally. Updating the prevalence and burden of LBP is important for researchers and policy makers. This paper presents, compares and contextualizes the global prevalence and years lived with disability (YLDs) of LBP by age, sex and region, from 1990 to 2017. Methods: Data were extracted from the GBD (the Global Burden of Disease, Injuries, and Risk Factors Study) 2017 Study. Age, sex and region-specific analyses were conducted to estimate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
687
5
43

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 961 publications
(748 citation statements)
references
References 41 publications
(56 reference statements)
13
687
5
43
Order By: Relevance
“…The global health policy landscape has evolved from the 20th century into the 21 st century, reflecting dramatic changes in population health over this period. Although the burden of disease associated with MSK conditions has remained high over time, evidenced for example by low back pain being the leading cause of global disability since Global Burden of Disease (GBD) study measurements commenced in 1990 [137], it was not prioritised as a global health priority in the 20th century. Whereas priorities for the 20th century largely focussed on communicable diseases such as HIV, nutritional deficiency disorders, maternal and child health and injury and trauma associated with war, the issues impacting human health in the 21st century have evolved, creating new and complex challenges for health systems at all stages of maturity [40].…”
Section: Evolving Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…The global health policy landscape has evolved from the 20th century into the 21 st century, reflecting dramatic changes in population health over this period. Although the burden of disease associated with MSK conditions has remained high over time, evidenced for example by low back pain being the leading cause of global disability since Global Burden of Disease (GBD) study measurements commenced in 1990 [137], it was not prioritised as a global health priority in the 20th century. Whereas priorities for the 20th century largely focussed on communicable diseases such as HIV, nutritional deficiency disorders, maternal and child health and injury and trauma associated with war, the issues impacting human health in the 21st century have evolved, creating new and complex challenges for health systems at all stages of maturity [40].…”
Section: Evolving Challengesmentioning
confidence: 99%
“…From a conviction of the unrecognised burden, this coalition has provided independent evidence that MSK conditions are the greatest cause of disability in most parts of the world, which is influencing priorities at the policy level [ 54 ]. This theme of work has continued since the Decade concluded in 2010 through a range of global initiatives in addition to the ongoing activities of G-MUSC; for example through the Lancet Series on Low Back Pain [ 65 ], dedicated reports on MSK burden of disease [ 55 , [107] , [108] , [109] , [110] , [111] , [112] , [113] , 137 ] and advocacy initiatives from international organisations such as the Fragility Fracture Network [ 114 ], International Osteoporosis Foundation [ 115 ] and the International Association for the Study of Pain.…”
Section: Harnessing Global Health Network To Influence the Global Hementioning
confidence: 99%
“…A total of 80% of the world population suffer from low back pain (LBP) which is considered the most significant cause of disability, resulting in a negative socioeconomic impact [1,2]. In terms of disability-adjusted life years, LBP incurs a substantial burden over other health-related conditions [3,4]. Although LBP is more common in patients above 65 years old [5,6], it can start as early as in the late teenage years [7].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] LBP was the fifth leading cause of disability-adjusted life years (DALYs) among American populations in 2016 and the first leading cause of years lived with disability (YLD). 4,5 About 50-85% of the population has back pain at some point in their whole life. 6,7 Previous studies have shown intervertebral disk degeneration (IDD) is one of the major reasons that contributed to LBP.…”
Section: Introductionmentioning
confidence: 99%